Anisotropic superconducting property studies of single crystal PbTaSe2. (18th January 2017) - Sankar, Raman; Rao, G Narsinga; Muthuselvam, I Panneer; Chang, Tay-Rong; Jeng, H T; Murugan, G Senthil; Lee, Wei-Li; Chou, F C
Abstract: The anisotropic superconducting properties of PbTaSe2 single crystal is reported. Superconductivity with T c = 3.83 ± 0.02 K has been characterized fully with electrical resistivity ρ ( T ), magnetic susceptibility χ ( T ), and specific heat C p ( T ) measurements using single crystal samples. The superconductivity is type-II with lower critical field H c1 and upper critical field H c2 of 65 and 450 Oe ( H ⊥ to the ab -plane), 140 and 1500 Oe ( H || to the ab -plane), respectively. These results indicate that the superconductivity of PbTaSe2 is anisotropic. The superconducting anisotropy, electron–phonon coupling λ ep, superconducting energy gap Δ0, and the specific heat jump Δ C / γT c at T c confirms that PbTaSe2 can be categorized as a bulk superconductor.